Diagnosing and financial evaluation of the Algerian banking sector - Chaabnia, Souad; Saadane, Assia; Amari, Saliha (Technium Social Sciences Journal, 2022)
This study aims at shedding some light uponat the financial situation of the Algerian banks through the use of a set of traditional criteria in order to diagnose and evaluate their financial performance. This study relied on the descriptive analytical method through collecting, organizing, and analyzing information in accordance with the research requirements. This study has improved. that the financial position of the Algerian banking system is still comfortable despite all the structural and organizational imbalances that the latter suffers from. The study has also revealed some weaknesses that must be overcome in order to develop this sector. If these imbalances are overcome as soon as possible, this will be positively reflected on all the financial criteria adopted in the evaluation process.